PENINGKATAN KEMAMPUAN GURU-GURU DALAM PENGAJARAN MATEMATIKA DAN SAINS DALAM BAHASA INGGRIS DI SMPN 10 DENPASAR MELALUI MEDIA PELATIHAN - D. P. E, Nilakusmawati; Dharmawan, K. (Buletin Udayana Mengabdi; Vol 11 No 2 (2012): Volume 11 No.2 – September 2012, 2012)
The Community service concerning with “training of teaching mathematics and science in English” was held for teachers, in SMPN 10 Denpasar. The aims of this activity are introduce ways of teaching mathematics and science in English for school teachers toward independent category RSBI in SMP 10 Denpasar. The method used was in the form of training, presentation and teaching practices. Data was analyzed using descriptive qualitative, quantitative and inferential statistical analysis. Hypotheses were tested by t-test. Results of analysis of data obtained during the activity, showed : (1) Mean score of pre test is 5.229, and mean of post test is 7.438. The correlation between score of pre test and post test equal to 0.845, with probability 0.000, meaning that there are correlation which are positive and significant. The results of hypothesis testing, obtained t value is -5.673 with a probability of 0.000. Since the probability of <0.05, then Ho is rejected, meaning that the provision of training teaching mathematics and science in English significantly affect the increase of knowledge of teachers as participant of training regarding the ways of teaching mathematics and science in English at SMP 10 Denpasar.